How Successful Has the Stability and Growth Pact Been? An Empirical Analysis - Andrew Hughes Hallett; John Lewis (Vierteljahrshefte zur Wirtschaftsforschung, 2004)
Prior to EMU, fiscal policy within the EU was disciplined by the threat of exclusion of the single currency; post-EMU, discipline has been exerted through the provisions of the Stability and Growth Pact. In this paper, we contrast the discipline induced by the two separate regimes on three specific criteria: the probability of violating the 3% deficit limit, the probability of commencing a budgetary consolidation, and the longevity of a budgetary consolidation once undertaken. We find that the runup to EMU did lead to a marked increase in the probability of commencing consolidations. However, once inside EMU, this discipline gradually slipped - with the longevity of consolidations being reduced year on year, and the probability of violating the 3% limit rising year on year. By 2004, the cumulative slippage meant that the initial disciplinary benefits of joining the Euro were completely eroded. Growth accounting analysis reveals that the source of the problem was the reliance on growth to meet budgetary targets and a corresponding failure to build up adequate surpluses at the top of the cycle. – – Vor dem Beitritt zur EWU wurde die Fiskalpolitik durch den möglichen Ausschluss einer einzelnen Währung diszipliniert. Nach dem Beitritt erfolgt diese Disziplinierung durch den Stabilitäts- und Wachstumspakt. Im vorliegenden Aufsatz wird die in beiden Regimen ausgeübte Disziplinierung an drei verschiedenen Kriterien überprüft: der Wahrscheinlichkeit, das 3 %-Kriterium zu verletzen, der Wahrscheinlichkeit, eine Konsolidierung einzuleiten, sowie der Langlebigkeit einmal unternommener Konsolidierung. Im Vorlauf zur EWU stieg die Wahrscheinlichkeit, Konsolidierungen einzuleiten. Waren die Länder jedoch erst einmal aufgenommen, sank die Disziplin deutlich, die Nachhaltigkeit der Konsolidierung nahm ab, und die Wahrscheinlichkeit für die Verletzung des 3 %-Kriteriums stieg. Im Jahre 2004 waren die disziplinierenden Vorzüge des Beitritts zur EWU aufgebraucht. Die Analyse zeigt, dass die Quelle des Problems darin lag, auf Wachstumseffekte zur Konsolidierung gebaut und keine angemessenen Übersc
Keywords: 330; Finanzpolitik; Haushaltskonsolidierung; Eurozone; EU-Staaten; Europäischer Stabilitätsmechanismus